1986
DOI: 10.1016/s0022-5347(17)45519-4
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy Following Radical Prostatectomy: Results and Complications

Abstract: Between 1954 and 1978, 148 patients underwent radical perineal prostatectomy for adenocarcinoma clinically confined to the prostate gland. This report is based on 45 of these patients with microscopic extension of disease beyond the gland and a minimum 5-year followup. Of the patients 22 received adjuvant external beam radiation therapy and 23 did not. The groups were comparable with regard to significant prognostic variables. Patient selection was by surgeon preference. Local recurrences were seen in 1 of 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…The few patients whose surgical margins are negative but progress (without positive seminal vesicle) are likely pathologic sampling errors as showed by Humphrey et al [14], Capsular effraction increases the rates of positive sur gical margins and biological progression. If there is an extraglandular involvement, 52% [16] to 60% [14] of the patients have positive margins (69% in our series). In this study, 80% of the patients with extracapsular disease pro gress because of positive margins or unsuspected micro metastasis, but further follow-up will be necessary to establish the length of the disease-free interval after radi cal prostatectomy in patients with capsular effraction.…”
Section: Discussionmentioning
confidence: 54%
“…The few patients whose surgical margins are negative but progress (without positive seminal vesicle) are likely pathologic sampling errors as showed by Humphrey et al [14], Capsular effraction increases the rates of positive sur gical margins and biological progression. If there is an extraglandular involvement, 52% [16] to 60% [14] of the patients have positive margins (69% in our series). In this study, 80% of the patients with extracapsular disease pro gress because of positive margins or unsuspected micro metastasis, but further follow-up will be necessary to establish the length of the disease-free interval after radi cal prostatectomy in patients with capsular effraction.…”
Section: Discussionmentioning
confidence: 54%
“…Certain clinical trials of postoperative RT included patients with measurable prostate-specific antigen (PSA) levels; therefore, the term ''immediate postoperative RT'' should be preferred to ''adjuvant RT.'' Although immediate postoperative RT has been used to reduce the risk of recurrence for several years now, only a few retrospective series or case reports were found (2)(3)(4)(5)(6)(7)(8). However, in 2005 and 2006, two large, randomized, controlled studies (9,10) were published in full and a third (11) was published in abstract form; hence, retrospective series on this topic have not been discussed.…”
Section: Immediate Postprostatectomy Rtmentioning
confidence: 99%
“…Patients with elevated postoperative PSA levels, pelvic lymph node metastasis, seminal vesicle invasion, extracapsular tumor extension, high-grade tumor, or positive surgical margins can benefit from XRT [43,46]. Gibbons et al [47] reported a lower 5-year recurrence rate in patients with margin-positive disease who received XRT versus no therapy. Unfortunately there was no statistical analysis in this report.…”
Section: Management Of Margin-positive Diseasementioning
confidence: 99%